2018
DOI: 10.1007/s12035-018-0988-x
|View full text |Cite
|
Sign up to set email alerts
|

The Endo-Lysosomal System of Brain Endothelial Cells Is Influenced by Astrocytes In Vitro

Abstract: Receptor- and adsorptive-mediated transport through brain endothelial cells (BEC) of the blood-brain barrier (BBB) involves a complex array of subcellular vesicular structures, the endo-lysosomal system. It consists of several types of vesicles, such as early, recycling, and late endosomes, retromer-positive structures, and lysosomes. Since this system is important for receptor-mediated transcytosis of drugs across brain capillaries, our aim was to characterise the endo-lysosomal system in BEC with emphasis on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 81 publications
2
12
0
Order By: Relevance
“…TAMRA-Tat- N -dimer appeared to be taken up by the primary BCECs cultured on microscope slides to the same extent as TAMRA-Tat and TAMRA-Tat-NR2B9c, which contradicts the observed degree of uptake in the in vitro BBB model. Recently, Toth et al demonstrated that co-culture of BCECs with astrocytes affects the endo-lysosomal sorting system [ 42 ]. Whether the presence of the astrocytes affects the uptake of TAMRA-Tat- N -dimer in the co-culture BBB model, but not in the BCECs when cultured alone on microscope slides, requires further study before conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…TAMRA-Tat- N -dimer appeared to be taken up by the primary BCECs cultured on microscope slides to the same extent as TAMRA-Tat and TAMRA-Tat-NR2B9c, which contradicts the observed degree of uptake in the in vitro BBB model. Recently, Toth et al demonstrated that co-culture of BCECs with astrocytes affects the endo-lysosomal sorting system [ 42 ]. Whether the presence of the astrocytes affects the uptake of TAMRA-Tat- N -dimer in the co-culture BBB model, but not in the BCECs when cultured alone on microscope slides, requires further study before conclusions can be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that to improve the current understanding of BBB transcytosis and reveal the specific mechanisms of intracellular transport within BECs, it is necessary to adopt emerging technologies from the field of molecular cell biology, such as super-resolution microscopy, unbiased image analysis, and genome editing. The value of quantitative microscopy/image analysis for the BBB is highlighted by the findings on new mechanisms of transferrin receptor sorting [48] and on the regulation of the endo-lysosomal network of porcine BECs by astrocytes [113]. However, a major limitation of these studies is that they relied on two-dimensional cellular models that do not fully recapitulate the complex cellular architecture of the NVU.…”
Section: Open Questions and Challengesmentioning
confidence: 99%
“…Assumptions on their subcellular trafficking systems are based on observations from epithelial cell lines [3]. A recent study has pointed out that subcellular trafficking in primary BECs differs in detail from that of epithelial cells and therefore needs to be specifically examined [17]. Therefore, our aim was to investigate and characterize the endo-lysosomal system in the mouse bEnd.3 and the human hCMEC/D3 cell lines, which are widely used for the investigation of receptor-mediated transcytosis in in vitro drug transport studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our aim was to investigate and characterize the endo-lysosomal system in the mouse bEnd.3 and the human hCMEC/D3 cell lines, which are widely used for the investigation of receptor-mediated transcytosis in in vitro drug transport studies. In our previous study, we already described and characterized the endo-lysosomal structure of primary porcine BECs (PBEC) [17]. Consequently, we compare our observations on the cell lines to the PBEC model.…”
Section: Introductionmentioning
confidence: 99%